ANALISIS ALGORITMA C4.5 UNTUK PENENTUAN KELAYAKAN PELAMAR BEKERJA PADA PT INDOLAND - Tan, James; Elisa, Erlin (LPPM Universitas Putera Batam, 2021)
Judging from the development of science and technology (IPTEK) today, everyone is competing to catch up in business, expertise and education, especially the issue of globalization which is starting to enter Indonesia where quality resources are the benchmark in recruiting workers to join. labor. Based on data from the Central Statistics Agency (BPS) the number of the workforce in February 2020 was 137.91 million people, an increase of 1.73 million people compared to February 2019. Likewise in Batam, which is known as an industrial center which makes many job candidates come here to complain. fate. In this case the job owner must be more selective in increasing the criteria for employees to be accepted including PT. Indoland, this research will utilize the datamining algorithm analysis technique C4.5 to analyze the criteria for accepting prospective employees at PT. Indoland by using entorpy calculations and the highest profit from several the variables that have been determined, the criteria that greatly affect acceptance are education, age and health which are the main considerations.